Tanggung Jawab Pelajar Dalam Menghadapi Perkembangan Teknologi: Mengoptimalkan Manfaat Dan Menghindari Dampak Negatif - Yarmayani, Ayu (Jurnal Pengabdian Kepada Masyarakat Sosial Humaniora, 2024)
In the digital era, the need for learning that is flexible and accessible anytime and anywhere is increasing. This encourages the development of e-learning and other technology-based learning that allows learning not only limited to traditional classrooms. Many technology-based learning applications and tools have been developed to increase learning effectiveness. Tools such as simulations, educational games, learning videos, and interactive software enable students to understand the material in a more interesting and interactive way. The use of social media in learning can have a significant impact on the way students and teachers interact, access information, and develop digital skills. Social media can also be a means for sharing learning materials. This community service (PkM) activity aims to provide knowledge about the good use of technology so that every technology user can control them selves and minimize the negative impact of technology on students.